GE_GERICHTE P/7392/2018 vom 23. Juli 2018 - GE Cour de justice (2018)
ADMINISTRATION DES PREUVES ; QUALITÉ POUR AGIR ET RECOURIR ; POLICE ; DROIT D'ÊTRE ENTENDU | CPP.309.al2; CPP.312.al2; CPP.101; CPP.108; CPP.147